Implementation of Groundwater Tax Collection Based on Regional Regulation Number 10 of 2010 concerning Regional Taxes in Tangerang Regency - Afrilya Dwi Undaresta; Rahmawati; Juliannes Cadith (Epistemik Press, 2023)
This study focuses on the Implementation of Groundwater Tax Collection Based on Regional Regulation Number 10 of 2010 concerning Regional Taxes in Tangerang Regency which is motivated by the high activity of groundwater extraction in Tangerang Regency, but in reality, it is found that there is still low awareness of tax subjects to register as taxpayers and low compliance level of tax payable reporting. Therefore, this study aims to describe how the implementation of groundwater tax collection is based on regional regulation number 10 of 2010 concerning local taxes in Tangerang Regency. The research method used is a descriptive method with a qualitative approach. The results showed that the implementation of the collection was not optimal due to the lack of coordination between organizations, discretionary actions by lower-level bureaucrats that were not by regulations, and negative responses from groundwater taxpayers. This study concludes that the implementation of groundwater tax collection in Tangerang Regency is still not fully by tax regulations.